Keefektifan Patroli Unit Turjawali Satuan Sabhara Dalam Mencegah Terjadinya Pencurian Kendaraan Bermotor Roda Dua Di Wilayah Hukum Polres Bogor - Wanatirta, Aristo (Indonesian Journal of Police Studies, 2020)
Theft of two-wheeled motor vehicles (Curanmor) in Bogor regency has increased based on data obtained from the Bogor Criminal Police Criminal Unit. Curanmor two wheels are caused by economic factors. The lack of jobs has resulted in many unemployed people meeting their economic needs by committing crime, namely two-wheeled Curanmor. To prevent the two-wheeled Sabhara unit from being patrolled, the increase in two-wheeled Curanmor is still occurring, so the authors conducted a research at the Bogor Police Resort under the heading of the Sabjol Unit Turjawali unit patrol in preventing the two-wheeled Curanmor in the Bogor Police jurisdiction. In analyzing, the author uses several theories and concepts including Management Theory, Proactive Iceberg Theory, SWOT Theory, Patrol Concepts, and Effectiveness Concepts. By using a qualitative approach that is descriptive analytic, this is done in order to obtain the broadest picture of the problems that occur. The qualitative approach provides descriptive data in the form of words orally delivered by the primary source at the time of the interview, thus explaining the problem in depth. The results of the study found that: (1) the description of two-wheeled Curanmor caused by economic factors; (2) the implementation of Sabhara unit turjawali patrols in preventing effective two-wheeled Curanmor because the implementation of the tasks is not in accordance with the SOP; (3) The factors that influence the Turjawali Sabhara unit patrol in preventing the two-wheel chans are internal and external. Internal, such as human resources, budget, facilities and infrastructure and leadership policies. Externals such as community participation, cooperation, and social communication. Sara the author in this writing is to see Sabhara in order to report the limitations that affect the quality of patrol activities in preventing criminal acts. The suggestion to the Bogor Police Chief was to add personnel to the Sabbhara Bogor Police unit and its personnel to be given vocational education at Sabhara and to add fuel rations in patrol implementation.